Exploring University Students’ Difficulties in Writing English Academic Essay - Seprianus A. Nenotek; Zuvyati A. Tlonaen; Herry A. Manubulu (STAI Hubbulwathan Duri, 2022)
Academic wiring is one of the essential skills in academic writing, and it is vital to support students' self-development through opinion writing, grant essay writing and others. This study explores students' difficulties in writing English academic essays and the dominant challenges by using a mix-method approach. The qualitative is used to collect data, while the quantitative is used to find the difficulty percentage—the data analysis uses indicators from Brown (1999). The sample of this study was 30 students in the fifth semester of the English Education Study Program at Universitas Kristen Artha Wacana. The results showed that students still experienced serious difficulties in four aspects of academic writing; content, organization, discourse and mechanics. The most dominant difficulties (97%) were found in; 1) thesis statement; 2) related ideas; 3) development of ideas; and 4) use of description/cause and effect, comparison/contrast; 5) effective introduction; 6) topic sentence and 7) reference. Writing essays are challenging for students in the English Education Study program. Further research is recommended to investigate the causal factors and find practical strategies for teaching academic writing courses.